In vitro Activity of Cefiderocol against Globally Collected Carbapenem-Resistant Gram-Negative Bacteria Isolated from Urinary Track Source: SIDERO-CR-2014/2016. (4th October 2017) - Tsuji, Masakatsu; Hackel, Meredith; Echols, Roger; Yamano, Yoshinori; Sahm, Dan
Abstract: Background: Cefiderocol (S-649266) is a novel siderophore cephalosporin active against a wide variety of Gram-negative bacteria, not only Enterobacteriaceae but also non-fermenting bacteria such as Pseudomonas aeruginosa and Acinetobacter spp., including carbapenem-resistant strains. This potent activity is due to its efficient penetration through the outer membrane via active iron transporter systems and its high stability to both serine- and metallo-carbapenemases.This study evaluated the in vitro activity of cefiderocol and comparator agents against carbapenem-resistant clinical isolates collected from urinary track source in 2014–2016 from global countries. Methods / Methods : Carbapenem-resistant Enterobacteriaceae (CRE) and multidrug-resistant (MDR) non-fermenters (defined as resistant to imipenem, ciprofloxacin and amikacin) were collected globally from 2014 to 2016 by IHMA Inc. A total of 226 Enterobacteriaceae, 44 Acinetobacter baumannii, 45 P. aeruginosa, 7 Stenotrophomonas maltophilia and 1 Burkholderia cepacia isolated from a urinary track source were tested. MICs were determined for cefiderocol, cefepime (FEP), ceftazidime-avibactam (CZA), ceftolozane-tazobactam (C/T), ciprofloxacin (CIP), colistin (CST), and meropenem (MEM) by broth microdilution and interpreted according to CLSI 2016 guidelines. As recommended by CLSI, cefiderocol was tested in iron-depleted cation-adjusted Mueller Hinton broth. Quality control testing was performed on each day of testing by using E. coli ATCC25922 and P. aeruginosa ATCC27853. Results: MIC90 of cefiderocol against carbapenem-resistant Enterobacteriaceae, MDR P. aeruginosa, MDR A. baumannii, and S. maltophilia were 4 µg/mL or less. However, MEM, C/T and CZA had MIC90 s of >64µg/mL. Cefiderocol demonstrated potent in vitro activity against carbapenem-resistant Enterobacteriaceae, A. baumannii, and P. aeruginosa isolates collected from a UTI source. At 4 µg/mL or less, cefiderocol inhibited the growth of 95.8% of the isolates. Conclusion: These results strongly indicated that cefiderocol is a promising candidate for the treatment of the serious infections caused by cUTI isolated Gram-negative bacteria including carbapenem-resistant strains. Disclosures: M. Tsuji, Shionogi & Co.: Employee, Salary; M. Hackel, IHMA: Employee, Salary; R. Echols, Shionogi & CO., LTD.: Consultant, Consulting fee; Y. Yamano, Shionogi & Co.: Employee, Salary